Shenxian-Shengmai Oral Liquid Improves Sinoatrial Node Dysfunction through the PKC/NOX-2 Signaling Pathway. (12th April 2021) - Zhang, Heng; Hao, Miao; Li, Lingkang; Chen, Keyan; Qi, Jing; Chen, Wei; Cai, Xintong; Chen, Chen; Liu, Zhuang; Hou, Ping
Abstract : Sick sinus syndrome (SSS) is one of the common causes of cardiac syncope and sudden death; the occurrence of SSS is associated with the accumulation of ROS in the sinoatrial node (SAN). Shenxian-shengmai (SXSM) is a traditional Chinese medicine available as oral liquid that causes a significant increase in heart rate. The objective of this study is to observe the improvement of SXSM on SAN function in SSS mice and explore its potential mechanism. In the current study, SSS was simulated in mice by inducing SAN dysfunction using a micro-osmotic pump to inject angiotensin II (Ang II). The mouse model with SSS was used to determine the effect of SXSM on SAN function and to explore its potential mechanism. Furthermore, the HL-1 cell line, derived from mouse atrial myocytes, was used to simulate SAN pacemaker cells. Our results indicated that SXSM significantly increased the heart rate of SSS mice by reducing the AngII-induced accumulation of ROS in the SAN and by inhibiting the expression of HDAC4, thereby reducing the loss of HCN4, a critical component of the cardiac conduction system. MASSON staining revealed a reduction of SAN damage in SSS mice that were treated with SXSM compared with controls. In vitro experiments showed that AngII treatment caused an upregulation of the PKC/NOX-2 signaling pathway in HL-1 cells which could be prevented by pretreatment with SXSM. The protective effect of SXSM was attenuated upon treatment with the PCK agonist PMA. In conclusion, SXSM reduced the AngII-induced accumulation of ROS in the SAN through the PKC/NOX2 signaling pathway, improving the functioning of the SAN and preventing the decrease of heart rate in SSS mice.